Analisis Kesiapan dan Strategi Implementasi Universitas Korporat sebagai Sistem Pelatihan dan Pembelajaran ASN di Kementerian Perhubungan - Christofel J. A. Roringkon; Mala Sondang Silitonga (Jurnal Bina Praja, 2025)
Since the 1980s, Corporate University has evolved into a systematic human resource development strategy that integrates individual development with organizational goals. In the public sector, the New Public Management paradigm encourages the adoption of private-sector managerial practices to improve bureaucratic effectiveness, foster a culture of continuous learning, and strengthen institutional capabilities. In Indonesia, the implementation of Corporate University remains limited, particularly in technical ministries such as the Ministry of Transportation (Kemenhub), where some employees do not yet understand the Corporate University concept, training is not yet needs-based, and HR planning mechanisms such as the Individual Development Plan (IDP) and Human Capital Development Plan (HCDP) have not been consistently implemented. This study evaluates the institutional readiness of the Ministry of Transportation to implement in Corporate University using a mixed-methods approach with a Sequential Explanatory design. Quantitative analysis of 396 Civil Servants shows an average institutional readiness of 52.6% (Intermediate Low category), with the highest institutional structure (89.6%) and the lowest learning strategy (30.5%). Qualitative analysis confirms that despite strong structural foundations and technological support, the implementation of experiential learning, cross-unit collaboration, and system integration with IDP/HCDP remains limited. Triangulation results reveal a gap between formal readiness and operational effectiveness, emphasizing the need to strengthen coordination, internal capacity, and digital integration. These findings provide conceptual contributions to the Corporate University literature in the public sector and practical support for the Ministry of Transportation in building an adaptive, sustainable, and results-oriented civil servant learning system that supports innovative and collaborative bureaucratic transformation.